(untitled) (Revista de Ciências Agroveterinárias, 2018)
The concentration of elements in the soil may be anthropogenic or of natural origin, according to their source material and weathering degree. This study aimed to evaluate natural contents of cobalt and manganese in 56 representative soil profiles in the state of Santa Catarina that were not subjected to anthropic contamination, and relate them with the physical and chemical attributes of their corresponding soils. A total of 107 samples were used considering horizons A and B. Soil samples were subjected to digestion process, using the USEPA 3050 B method, and determined by inductively coupled plasma optical emission spectrometry (ICP OES). Cobalt and manganese levels differed between their classes, but not their horizons. In general, soils originated from basic igneous rocks presented higher concentrations of both elements. Latosols originated from basalt presented lower levels of Co and Mn than younger soils such as Chernozems, which have the same source material. The attributes silt/clay ratio, base sum and base saturation were positively correlated with the elements studied, aside from showing a strong correlation between each other.